2018
DOI: 10.7759/cureus.2901
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Streptococcus dysgalactiae Subsp. Dysgalactiae Human Zoonotic Infection

Abstract: Streptococcus dysgalactiae has two main subspecies: Streptococcus dysgalactiae subsp. equisimilus (SDSE) and Streptococcus dysgalactiae subsp. dysgalactiae (SDSD). The vast majority of human infections belonging to Streptococcus dysgalactiae have been associated with SDSE. There are only three cases of SDSD found in humans in literature. We present a case of SDSD cellulitis and bacteremia in a 49-year-old female patient from Houston, Texas with no major exposure to animals or trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 7 publications
(7 reference statements)
0
17
0
1
Order By: Relevance
“…Several genes are responsible for the increased virulence of these subspecies, providing the dissemination to a different host and propagating the infection persistent ( Rato et al, 2011 ; Alves-Barroco et al, 2018 ). This subspecies has been considered by some authors as an emerging zoonotic pathogen ( Chennapragada et al, 2018 ). Moreover, their biofilm-producing ability ( Alves-Barroco et al, 2019 ) can make them highly difficult to eradicate.…”
Section: Horizontal Gene Transfer Is Increased In Biofilmsmentioning
confidence: 99%
“…Several genes are responsible for the increased virulence of these subspecies, providing the dissemination to a different host and propagating the infection persistent ( Rato et al, 2011 ; Alves-Barroco et al, 2018 ). This subspecies has been considered by some authors as an emerging zoonotic pathogen ( Chennapragada et al, 2018 ). Moreover, their biofilm-producing ability ( Alves-Barroco et al, 2019 ) can make them highly difficult to eradicate.…”
Section: Horizontal Gene Transfer Is Increased In Biofilmsmentioning
confidence: 99%
“…SDSD has been reported to cause prosthetic joint infection [ 2 ], infective endocarditis [ 3 ], upper limb cellulitis [ 4 ], and lower limb cellulitis [ 5 ]. The patient with infective endocarditis reported by Jordal et al had a complicated course but he survived [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The latter was the name proposed for the strains of animal origin [1] and they are an uncommon cause of infection in humans. There are very few reports of this organism causing clinical infection in humans [2][3][4][5] and there are no reports of fulminant infection caused by SDSD. Here we report a middle-aged male who presented with features of right upper limb cellulitis and had septic shock.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to say whether this is related to the assumption made already at the clinical level that each strain of S. dysgalactiae isolated from humans is SDSE. However, researchers have shown that SDSD can infect humans [135]. The characteristics of the reported cases are detailed in Table 10.…”
Section: Streptococcus Dysgalactiae Subsp Dysgalactiae (Sdsd)mentioning
confidence: 99%
“…dysgalactiae isolated from humans is SDSE. However, researchers have shown that SDSD can infect humans [135]. The characteristics of the reported cases are detailed in .…”
Section: Introductionmentioning
confidence: 99%